2021
DOI: 10.3847/1538-4357/abec4f
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Formation of Pseudostreamers

Abstract: Streamers and pseudostreamers structure the corona at the largest scales, as seen in both eclipse and coronagraph white-light images. Their inverted-goblet appearance encloses broad coronal loops at the Sun and tapers to a narrow radial stalk away from the star. The streamer associated with the global solar dipole magnetic field is long-lived, predominantly contains a single arcade of nested loops within it, and separates opposite-polarity interplanetary magnetic fields with the heliospheric current sheet (HCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…The separatrix surfaces of two of these nulls together form a dome that encloses closed magnetic flux (red field lines in Figure 1(a) at around 45°north, and in Figure 3), while a portion of the separatrix of the third (central) null extends as a separatrix curtain out into the heliosphere (Titov et al 2011). Both spine lines of the eastern and western null points are in the closed field region, meaning that the S-Web structure that partitions the flux of the polar and midlatitude coronal holes is formed entirely by this separatrix surface (Scott et al 2021). These properties are stable throughout the simulations.…”
Section: Magnetic Field Geometry and Boundary Conditionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The separatrix surfaces of two of these nulls together form a dome that encloses closed magnetic flux (red field lines in Figure 1(a) at around 45°north, and in Figure 3), while a portion of the separatrix of the third (central) null extends as a separatrix curtain out into the heliosphere (Titov et al 2011). Both spine lines of the eastern and western null points are in the closed field region, meaning that the S-Web structure that partitions the flux of the polar and midlatitude coronal holes is formed entirely by this separatrix surface (Scott et al 2021). These properties are stable throughout the simulations.…”
Section: Magnetic Field Geometry and Boundary Conditionsmentioning
confidence: 97%
“…The S-Web has been studied, in detail, in recent years (Antiochos et al 2011;Titov et al 2011;Crooker et al 2012;Scott et al 2018Scott et al , 2019Scott et al , 2021, and these studies have shown that there are two primary types of open/closed boundaries that contribute to this Web and, thereby, serve as sources of slow wind. One that is always present is the helmet streamer belt and associated heliospheric current sheet (HCS).…”
Section: Introductionmentioning
confidence: 99%
“…3), while a portion of the separatrix of the third (central) null extends as a "separatrix curtain" out into the heliosphere (Titov et al 2011). Both spine lines of the eastern and western null points are in the closed-field region, meaning that the S-Web structure that partitions the flux of the polar and mid-latitude coronal holes is formed entirely by this separatrix surface (Scott et al 2021). These properties are stable throughout the simulations.…”
Section: Magnetic Field Geometry and Boundary Conditionsmentioning
confidence: 99%
“…The S-Web captures all the separatrix and quasi-separatrix surfaces due to the open-closed boundary and, thereby, indicates possible locations for slow wind in the heliosphere. The S-Web has been studied, in detail, in recent years (Antiochos et al 2011;Titov et al 2011;Crooker et al 2012;Scott et al 2018Scott et al , 2019Scott et al , 2021, and these studies have shown that there are two primary types of open-closed boundaries that contribute to this Web and, thereby, serve as sources of slow wind. One that is always present is the helmet streamer belt and associated heliospheric current sheet (HCS).…”
Section: Introductionmentioning
confidence: 99%
“…For plasma that originates from within a closed domain to escape across the open-closed boundary into an adjacent coronal hole depends on the process of interchange reconnection (Crooker et al 2002), whereby field lines from either side of the open-closed boundary undergo a change in connectivity so that a new flux tube is formed that extends from a footpoint within a previously closed region on the solar surface out into the open coronal-hole region and into the heliosphere and beyond. This process has been studied extensively in 3D magnetohydrodynamic (MHD) simulations of coronal streamers and pseudostreamers (e.g., Masson et al 2014;Higginson et al 2017;Aslanyan et al 2021;Scott et al 2021); however, these and similar studies have invoked simplistic fluid approximations for computational efficiency. Therefore, while the magnetic evolution is reasonably well understood, many questions remain concerning the associated plasma dynamics.…”
Section: Introductionmentioning
confidence: 99%